Differences in the level of media competency by type of education system - González-Cabrera, Catalina (2019)
Education in media literacy in Ecuador has gained special relevance in the last decade. Both academics and researchers have pointed out that the country also needs to reduce the digital divide; and train students, teachers and all members of society in the use and consumption of traditional and digital media. Previous studies show that the level of media competency differs by type of education system, whether it is private, co-financed or public. This research determines if the type of education system (regular urban education, regular rural education, and flexible and distance education) is an influential factor in the generation of competencies. Through a questionnaire and the corresponding statistical analysis, it was concluded that students who attended the regular education system within the city demonstrated a higher level of media competency compared to the other participants of the study. Differences were found in gender, age and level of media competency. Applying these results is important to improve public policies in education, training and access to the Internet and new technologies.